PENGARUH SIZE OF COMMISSIONER BOARD, BOARD GENDER DIVERSITY, DAN EDUCATION BACKGROUND OF THE BOARD TERHADAP PENGUNGKAPAN SUSTAINABILITY REPORTING - Puspitasari, Ananda; Purwohedi, Unggul; Sasmi, Aji Ahmadi (LPPM Universitas Bina Bangsa, 2023)
This study aims to examine and analyze the Size of Commissioner Board, Board Gender Diversity and Education Background of The Board on Sustainability Reporting Disclosure. This study uses secondary data sources derived from the company's annual report and sustainability report on manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2020-2022 with purposive sampling technique. A total final sample of 55 companies was obtained, so that the total observation data during 2020-2022 was 165 data. The analysis technique used is panel data regression analysis using Econometric Views 13 (EViews) software. The results of this study prove that the size of the commissioner board has a significant positive effect on sustainability reporting, board gender diversity has no effect on sustainability reporting, and the education background of the board has a significant positive effect on sustainability reporting